2017
DOI: 10.3390/en10020150
|View full text |Cite
|
Sign up to set email alerts
|

Application of Meta-Heuristic Techniques for Optimal Load Shedding in Islanded Distribution Network with High Penetration of Solar PV Generation

Abstract: Abstract:Recently, several environmental problems are beginning to affect all aspects of life. For this reason, many governments and international agencies have expressed great interest in using more renewable energy sources (RESs). However, integrating more RESs with distribution networks resulted in several critical problems vis-à-vis the frequency stability, which might lead to a complete blackout if not properly treated. Therefore, this paper proposed a new Under Frequency Load Shedding (UFLS) scheme for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Every optimization technique has their own limitations as given in Table 4, so it can be concluded that hybrid optimization techniques may overcome these limitations by combining their strengths, which results in more accurate and optimal solutions to practical engineering problems. 148 A new voltage stability index for online monitoring and load shedding is proposed in another study. Moreover, an improved algorithm for optimal load shedding with voltage stability as constraint presented in a previous study.…”
Section: Recent Approaches For Uvlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Every optimization technique has their own limitations as given in Table 4, so it can be concluded that hybrid optimization techniques may overcome these limitations by combining their strengths, which results in more accurate and optimal solutions to practical engineering problems. 148 A new voltage stability index for online monitoring and load shedding is proposed in another study. Moreover, an improved algorithm for optimal load shedding with voltage stability as constraint presented in a previous study.…”
Section: Recent Approaches For Uvlsmentioning
confidence: 99%
“…Several meta-heuristic techniques to optimize load shedding in the minimum possible time while satisfying all the power system constraints have been proposed in the literature. 148 A new voltage stability index for online monitoring and load shedding is proposed in another study. 87 Similarly, the authors of previous research 76 propose a technique to identify the critical lines in a power system for optimal load shedding.…”
Section: Recent Approaches For Uvlsmentioning
confidence: 99%
“…It was highlighted in [18] that the output power of photovoltaic and wind generation might change during the UFLS period, thus the power generation variations during the UFLS were considered. In [19], the authors proposed an improved UFLS in the islanded distribution network with high penetration of solar photovoltaic generation. Also, the approach of [20] focused on the effects of high photovoltaic penetration on the distributed system, but all of the simulations were carried out in the distributed grid.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, the global accumulative installed capacity increased from 1.4 GW in 2000 to around 102.2 GW in 2012 [6]. PV technology is expected to play a significant role in future developments in developed and developing countries [7]. As more attention is being focused on their viability from technical and economical assessment [8].…”
Section: Introductionmentioning
confidence: 99%